An exploratory factor analysis and reliability analysis among Malaysian elderly - Zulaikha Abdul Razak; Noorzilawati binti Sahak (International Journal of Public Health Science (IJPHS), 2023)
Low awareness and underdeveloped instruments evaluating elderly Malaysians’ well-being, social support, and independence necessitate lubben social network scale (LSNS), social provisions scale (SPS), Katz activities of daily living (ADL), and life satisfaction index (LSI) development and evaluation involving 201 60-year-old males and females (purposive samples) in Kuching and Bintulu participated (June to August 2022). Exploratory factor analysis (EFA) examined the construct validity of LSNS, SPS, Katz ADL, and LSI, whereas principal axis factoring (paf) and orthogonal (varimax) rotation with Kaiser Normalisation validated their psychometric properties and internal consistency reliability using Cronbach’s alpha. Social integration (0.94), reassurance of worth (0.91), attachment (0.90), sense of reliable alliance (0.78), and guidance (0.74) have eigenvalues >1 in the SPS-10 EFA; good Cronbach’s alpha reliability values. Family (0.77) and friends (0.73) of LSNS-6 factors have eigenvalues >1, good Cronbach’s alpha reliability values. Acceptance-contentment (0.87) and Achievement-fulfilment (0.72) had eigenvalues >1 in the Life Satisfaction Index-Z EFA, good Cronbach’s alpha reliability values. In the EFA of Katz ADL, single items with factor loadings ≥0.5: bathing, dressing, toileting, transferring, and feeding; loadings <0.3: Continence; Cronbach’s alpha reliability value was 0.95. LSNS, SPS, Katz ADL, and LSI were valid and reliable instruments measuring elderly well-being, social support, and independence. Confirmatory factor analyses will revalidate it in different populations.